Effect of silver in thiosulfate leaching of gold-silver alloys in the presence of copper and ammonia relative to pure gold and silver. - Oraby, E.; Browner, Richard; Nikraz, Hamid (Maney Publishing, 2014)
One promising alternative to cyanide for the leaching of gold is thiosulfate due to its low toxicity and efficiency in leaching gold from low-grade and carbonaceous ores and concentrates. Much of the published research focuses to optimizing the reagent concentrations to develop a suitable process for industrial applications. However, there are few studies on the effect of silver content on gold dissolution rate in the thiosulfate leaching system. In this paper, the dissolution rate of pure gold, pure silver, and gold–silver alloys of silver compositions, 4, 8, 20, and 50 wt% are reported. The effects of various parameters on the rate of gold and silver dissolution have been determined. The results show that the pure silver dissolution rate is around 6.89 times greater than pure gold. The results show that silver enhances gold dissolution in thiosulfate solutions. The dissolution rate of gold from pure gold is higher than that obtained from 4% and 8% silver alloys, but less than that obtained from 20% and 50% silver alloys.